Characterization of total suspended solid dynamics in a large shallow lake using long‐term daily satellite images. Issue 21 (1st August 2019) - Hoshikawa, Keisuke; Fujihara, Yoichi; Siev, Sokly; Arai, Seiya; Nakamura, Takashi; Fujii, Hideto; Sok, Ty; Yoshimura, Chihiro
Abstract: Large, shallow‐water lakes located on floodplains play an important role in creating highly productive ecosystems and are prone to high concentrations of suspended solids due to sediment resuspension. In this study, the aim was to determine the dominant processes governing the total suspended solid (TSS) concentration at the water surface in Tonle Sap Lake, Cambodia, which is a large, shallow‐water lake. Satellite remotely sensed daily reflectance data from 2003 to 2017 were used. Seasonal changes in TSS concentration indicated that bottom sediment resuspension during dry seasons was mostly caused by wind and the TSS concentration was closely correlated with the water depth of the lake. The TSS concentration during flood periods was controlled by both wind and inflow currents from the Tonle Sap River. Additionally, we confirmed that surface/subsurface flow with a low TSS concentration from forests on the floodplain lowered the TSS concentration year round, except during August and September. This fact implied that the floodplain forest area decrease may increase the lake TSS concentration. An analysis of the long‐term changes in TSS indicated that a decrease in the water level during flood periods resulted in the high TSS concentrations observed during the subsequent dry periods. Therefore, climate change and water resource development, which are likely to cause water level reductions in the Mekong River during flood periods, may increase the TSS concentration in Tonle Sap Lake, particularly during the dry season. Abstract : Resuspension of bottom sediments was mainly induced by wind and by the inflow current, and their relative contribution changed seasonally. The potential for resuspension was strongly governed by the water depth. Surface/subsurface flow with low concentration of total suspended solids (TSS) from the forests on the floodplains lowered the TSS concentration throughout the year, except during the mid‐flood season.